2013
DOI: 10.5665/sleep.2710
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Accelerates Delay-Related Loss of Visual Short-Term Memories Without Affecting Precision

Abstract: Visual short-term memory is compromised during sleep deprivation, an effect compounded by delay. However, when memories are retrieved, they tend to be intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 62 publications
4
21
0
Order By: Relevance
“…However, other reports have indicated a decrease in the activation of the parietal cortex after sleep deprivation (Almklov et al, 2015). Moreover, the results revealed that the decrease in activation was significantly correlated with a decrease in short-term memory after sleep deprivation (Adrienne, 2013; Xie et al, 2015; Nicolas et al, 2016; Julien et al, 2017). Previous study using an n-back task to test WM in participants who had been sleep-deprived for 24 h found that sleep deprivation leads to a reduction in metabolic activity in the brain’s regional network (prefrontal cortex, anterior cingulate gyrus, thalamus, and cerebellum) mainly involved in information processing and executive control (Choo et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…However, other reports have indicated a decrease in the activation of the parietal cortex after sleep deprivation (Almklov et al, 2015). Moreover, the results revealed that the decrease in activation was significantly correlated with a decrease in short-term memory after sleep deprivation (Adrienne, 2013; Xie et al, 2015; Nicolas et al, 2016; Julien et al, 2017). Previous study using an n-back task to test WM in participants who had been sleep-deprived for 24 h found that sleep deprivation leads to a reduction in metabolic activity in the brain’s regional network (prefrontal cortex, anterior cingulate gyrus, thalamus, and cerebellum) mainly involved in information processing and executive control (Choo et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Recently, it was shown that an improvement of WM perfomance after post-training sleep compared with an equivalent period of wakefulness, suggesting the beneficial effects of sleep on WM ability (Kuriyama et al, 2008). Similarly, it has also been demonstrated that our ability to attend to and maintain information in WM is severely affected by sleep deprivation (Chee and Choo, 2004;Drummond et al, 2012;Wee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This sets a major constraint on a wide range of cognitive and affective processes, such as attention (Kane, Poole, Tuholski, & Engle, 2006), fluid intelligence (Conway, Cowan, Bunting, Therriault, & Minkoff, 2002), processing of affective information (Lynn et al, 2016; Xie et al, 2017), and emotional regulation (Schmeichel, Volokhov, & Demaree, 2008). In addition, compromised WM is also frequently associated with declines in various health-related factors, such as poor sleep quality (e.g., Wee, Asplund, & Chee, 2013), depressed mood (e.g., Xie et al, 2018a), and age (e.g., Peich, Husain, & Bays, 2013), suggesting the importance of WM assessment in translational research.…”
mentioning
confidence: 99%
“…For example, naturally-occurring and experimentally-induced sleep loss can significantly impair WM (Chee & Chuah, 2007; Smith, McEvoy, & Gevins, 2002; F. Waters & Bucks, 2011; Wee et al, 2013). Although these impairments have been taken as evidence for reduced WM capacity (i.e., the amount of information maintained in WM), a reduction in memory quality might also account for these findings (see Xie & Zhang, 2016; 2017a; 2017b; Zhang & Luck, 2009; 2011 for some discussions).…”
mentioning
confidence: 99%